Opportunities and barriers to on-farm composting and compost application: A case study from northwestern Europe. (February 2016) - Viaene, J.; Van Lancker, J.; Vandecasteele, B.; Willekens, K.; Bijttebier, J.; Ruysschaert, G.; De Neve, S.; Reubens, B.
Highlights: Limited compost use despite farmers' recognition of the benefits. Mixed method approach used to reveal barriers to compost use in agriculture. Twenty-eight barriers were revealed, analyzed and categorized. The most prevalent barriers are either financial, institutional or informational. Five recommendations to potentially alleviate some of the barriers to compost use. Abstract: Maintaining and increasing soil quality and fertility in a sustainable way is an important challenge for modern agriculture. The burgeoning bioeconomy is likely to put further pressure on soil resources unless they are managed carefully. Compost has the potential to be an effective soil improver because of its multiple beneficial effects on soil quality. Additionally, it fits within the bioeconomy vision because it can valorize biomass from prior biomass processing or valorize biomass unsuitable for other processes. However, compost is rarely used in intensive agriculture, especially in regions with high manure surpluses. The aim of this research is to identify the barriers to on-farm composting and the application of compost in agriculture, using a mixed method approach for the case of Flanders. The significance of the 28 identified barriers is analyzed and they are categorized as market and financial, policy and institutional, scientific and technological and informational and behavioral barriers. More specifically, the shortage of woody biomass, strict regulation, considerable financial and time investment, and lack of experience and knowledge are hindering on-farm composting. The complex regulation, manure surplus, variable availability and transport of compost, and variable compost quality and composition are barriers to apply compost. In conclusion, five recommendations are suggested that could alleviate certain hindering factors and thus increase attractiveness of compost use in agriculture.